Optimization of a Marker Gas for Analyzing and Predicting the Spontaneous Combustion Period of Coking Coal - Peizhong Lu; Yuxuan Huang; Peng Jin; Shouguo Yang; Man Wang; Xiaochuan Wang (Energies, 2023)
The adequate assessment of the spontaneous combustion and oxidation characteristics of coking coal can help to reduce its spontaneous combustion potential. In this study, the natural ignition period of the Hex coking coal seam at Ping Coal was calculated based on the programmed-temperature-rise test and the thermal property parameters measured during the spontaneous combustion of the coal. Typical gas concentrations were measured at different oxygen concentrations and coal particle sizes to investigate the changes in the oxygen, carbon–oxygen, and hydrocarbon gas concentrations during the low-temperature oxidation of the coking coal and to determine the indicator gases at different oxidation stages. The following results were obtained: The minimum critical oxygen concentration required for spontaneous ignition was 8%, and fire prevention measures should be implemented below 200 °C. When the temperature of the coal sample reaches 50–60 °C, the rates of CO and CO2 production increase, and when the temperature of the coal sample reaches 100–120 °C, the spontaneous combustion and oxidation of the coal generates alkane gas, in which the coal particle size has a negligible effect on the concentration of each generated gas. CO and C2H4 were selected as the indicator gases for different coking coal oxidation stages, and C2H6 and the C2H4/C2H6 ratio were used as secondary indicators to assist in the analysis. Utilizing the enhanced mathematical model for the shortest spontaneous combustion period of coal seams, in conjunction with a programmed-temperature test device, experimental calculations were conducted to determine the adiabatic spontaneous combustion period. The results indicate that the natural ignition period for the Hex coking coal seam at Ping Coal is approximately 60 days, representing a brief timeframe, and the coal seam is characterized by a high risk of spontaneous combustion.